The Relationship between Fiscal Policy and Civil Liberty on Per capita GDP in Indonesia during 1980-2018 - Sari, Vita Kartika; Cahyadin, Malik (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 1, Februari 2022 (pp.1-161)DO - 10.24843/JEKT.2022.v15.i01.p02, 2022)
ABSTRACT Fiscal policy has a contribution to community welfare. Many empirical findings explained the relationship between the fiscal component and per capita income. In addition, civil liberty is a driving factor in economic life. Thus, this study estimated the relationship between fiscal policy and civil liberty on Per capita GDP in Indonesia during 1980-2018. The VAR and Bayesian VAR estimation models were selected and relevant to the a-theoretic economic variables. The empirical findings showed that the tax ratio contributed significantly to inhibit the increase in Per capita GDP, barriers to parties resulted in damaging Per capita GDP, but access to justice improved Per capita GDP. Thus, the Indonesian government should be able to encourage fiscal allocations for strategic and productive programs. In addition, the Indonesian government should also protect and guarantee civil liberties in accordance with applicable laws and regulations. Key words : government expenditure, tax ratio, external debt, civil liberty, Per capita GDP JEL Classification : E01, E02,  E62, H63